Non-chemisorbed gold–sulfur binding prevails in self-assembled monolayers - Inkpen, Michael S.; Liu, Zhen–Fei; Li, Haixing; Campos, Luis M.; Neaton, Jeffrey B.; Venkataraman, Latha (Nature chemistry, 2019)
Gold–thiol contacts are ubiquitous across the physical and biological sciences in connecting organic molecules to surfaces. When thiols bind to gold in self-assembled monolayers (SAMs) the fate of the hydrogen remains a subject of profound debate—with implications for our understanding of their physical properties, spectroscopic features and formation mechanism(s). Exploiting measurements of the transmission through a molecular junction, which is highly sensitive to the nature of the molecule–electrode contact, we demonstrate here that the nature of the gold–sulfur bond in SAMs can be probed via single-molecule conductance measurements. Critically, we find that SAM measurements of dithiol-terminated molecular junctions yield a significantly lower conductance than solution measurements of the same molecule. Through numerous control experiments, conductance noise analysis and transport calculations based on density functional theory, we show that the gold–sulfur bond in SAMs prepared from the solution deposition of dithiols does not have chemisorbed character, which strongly suggests that under these widely used preparation conditions the hydrogen is retained. Gold–thiol contacts are ubiquitous across the physical and biological sciences, connecting organic molecules to surfaces. Now, conductance measurements of different sulfur-bound single-molecule junctions show that thiols—in contrast to the prevailing view—are not chemisorbed on gold, which strongly suggests that the thiol hydrogen is retained.